Endodontic teaching in Philippine dental schools - Cruz, E.V.
This study aims to evaluate the pattern of undergraduate endodontic teaching in the Philippine dental schools.
Data were gathered by sending questionnaires to the deans of the 23 dental schools in the country to determine details of the teaching of root canal treatment in permanent teeth. the covering letter requested that endodontic staff complete the questionnaire.
Similarities were observed in the timing of undergraduate endodontic teaching, working length determination, and root canal preparation technique. Irrigating fluids recommended included one or a combination of the following: sodium hypochlorite, hydrogen peroxide, distilled water and EDTA. The root canal medicaments popularly employed were CMCP and eugenol. Most schools used slow-setting zinc oxide eugenol cement as sealer. Differences between schools were noted in the laboratory component of the course. The time alloted for the laboratory exercises, as well as the number of teeth used, differed greatly between each school. An inadequate tutor to student ratio was noted in the majority of schools. Teaching aids were limited and, in most instances, produced by faculty members. Most faculty members teaching endodontics had no special training.
The results of this study have demonstrated that there is a need to review endodontic teaching in the majority of the Philippine dental schools to ensure that the course content and curriculum employed by all schools meet specified standards and that appropriate measures should be considered to enhance the learning experience of students.
Keywords: Endodontics -- Study and teaching; Root canal treatment